Infrared spectroscopy as a compliment to X-ray diffraction for zeolite examination - Tomlinson, Sean R.; McGown, Ty; Schlup, John; Anthony, Jennifer L. (My University, 2011)
X-ray diffraction is commonly used to examine zeolite structure, but it is unable to see small changes in the long-or short-range structure. Infrared spectroscopy is used to examine changes in the long-and short-range structure of zeolite. Structural changes in zeolite CIT-6 and derivatives upon chemical treatment are identified with mid-and far-infrared spectroscopy. Differences in the local structure of the sample are observed in the mid-and far-infrared spectra.
Keywords: Zeolite; Infrared spectroscopy; X-ray diffraction; Aluminosilicate; Mid-infrared; Far-infrared